Impact of hydrophobic additives in macroplastics and trace metal contamination on Kuwait's coastal beaches - Abdul Hadi E. Bu-Olayan; B.V. Thomas (Kuwait Journal of Science)
The global rise in macroplastic waste has adversely affected Kuwait's beaches, presenting potential threats to the marine ecosystem. In this study, debris samples were collected and analyzed from eleven beach sites between 2022 and 2024. Macroplastics distributed across the studied sites were more abundant in the winter (76 %) than in the summer (59 %) seasons. The polypropylene items were highly apportioned (25 %) among the seven identified polymers in this study. Among the sites, macroplastics recovered from the S3 (intertidal mudflats, fishing, wastewater drains), S4 (recreation), and S9 (industries) areas showed high mean concentrations of Cr (512.62 μg/kg), Ni (248.49 μg/kg), and Zn (36.04 μg/kg) compared to the other analyzed metals. The indices outlined in this study reflected the characteristics of occupational activities, the negligence of beachgoers towards pollution, the presence of seven macroplastics types, impact of additive pollutants, and were corroborated by assessments of clean coastal (CCI), polymer abundance (PAI), and polymer hazardous (PHI) indices. Furthermore, observations showed that hydrological factors and seasonal variations influenced the abundance of macroplastics, validating macroplastics as a beach pollutant indicator. Conjecturing the apportionment and futuristic escalation of macroplastics pollution threats, this study depicts the salient mitigation strategies to decrease macroplastics in the marine environment.